1999
DOI: 10.1182/blood.v93.3.906.403k24_906_908
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Common Polymorphism in the Factor XIII Gene With Venous Thrombosis

Abstract: We have shown an association between a common mutation in the factor XIII a-subunit gene, coding for an amino acid change, 3 amino acids from the thrombin activation site (factor XIII Val34Leu) that may protect against myocardial infarction and predisposes to intracranial hemorrhage. To investigate the possible role of factor XIII Val34Leu in the pathogenesis of venous thromboembolism (VTE) and potential interactions with factor V Leiden (FV:Q506) and prothrombin G → A 20210, we studied 221 patients with a his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
2
7

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 6 publications
5
71
2
7
Order By: Relevance
“…One of the variations in the FXIII A gene, the Val34Leu polymorphism, has been correlated with thrombosis in a case–control study of 221 patients. Patients with thrombosis had an increased prevalence of the Val/Val genotype and a lower prevalence of the Val/Leu phenotype 56 . The study also showed that homozygous individuals carry a significantly higher activity of the enzyme than individuals with the wildtype genotype and heterozygous carry an intermediate value.…”
Section: Factor XIIImentioning
confidence: 76%
“…One of the variations in the FXIII A gene, the Val34Leu polymorphism, has been correlated with thrombosis in a case–control study of 221 patients. Patients with thrombosis had an increased prevalence of the Val/Val genotype and a lower prevalence of the Val/Leu phenotype 56 . The study also showed that homozygous individuals carry a significantly higher activity of the enzyme than individuals with the wildtype genotype and heterozygous carry an intermediate value.…”
Section: Factor XIIImentioning
confidence: 76%
“…The presence of Leu instead of Val within codon 34 (FXIIIVal34Leu) in the 2 nd exon of the FXIII A-subunit gene has been associated with high FXIII specific activity [Anwar et al 1999]. The FXIIIVal34Leu (G → T) mutation has been associated with myocardial and brain infarction Elbaz et al 2000;Rallidis et al 2008;Shafey et al 2007;Wartiovaara et al 1999], venous thrombosis, and familial thrombophilia [Catto et al 1999;Balogh et al 2000;Franco et al 2000;Vossen and Rosendaal 2005;Wells et al 2006]. It has been observed that severe FXIII deficiency is a rare homozygous disorder, but, heterozygous FXIII deficiency is more common [Ichinose and Davie 1988;.…”
Section: Resultsmentioning
confidence: 99%
“…To date, there have been 2 studies analyzing the possible association of FXIII Val34Leu polymorphism with venous thrombosis. Catto et al 15 demonstrated that the Leu34 allele represents a significant protection against venous thrombosis. Franco et al 16 reported that the protective effect was restricted to homozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Protection against venous thrombosis by the Leu34 allele has also been reported. 15,16 The biochemical consequences of FXIII-A Val34Leu polymorphism are unknown, and no scientifically sound hypothesis for the biochemical mechanism of such protective effect has been offered. In theory, a polymorphism may influence the plasma level of FXIII, the process of activation, and the specific transglutaminase activity of FXIIIa.…”
Section: And Muszbek Et Al 2 )mentioning
confidence: 99%